004 Fluoride and bone cancer: is there a link? Small-area analyses of primary bone cancer in 0–49-year-olds in Great Britain, 1980–2005. (16th November 2010) - Blakey, K; Feltbower, R G; Parslow, R C; James, P W; Pozo, B Gómez; Stiller, C; Vincent, T J; Norman, P; McKinney, P A; Murphy, M F; Craft, A W; McNally, R J Q
Abstract : Objective: To analyse the putative association between incidence of primary bone cancer diagnosed in 0–49 year olds in Great Britain (GB) in 1980–2005 and fluoride in drinking water. The analyses focussed on osteosarcoma and Ewing sarcoma. Design: The study accessed multiple data sources including population census, digital boundary, postcode directory and fluoride monitoring at water supply zone level data. Incidence data from all 10 regional cancer registries were accessed and analysed by census ward. Residential postcode was used as a proxy for population distribution and the basis for making all census data compatible with 2001 census geography. Postcode distributions were also used to link water supply zones to census wards for England and Wales and postcode sectors for Scotland and enabled a fluoride level to be assigned to each census small-area in GB. Setting: GB. Participants: Data from patients (0 to 49 years) diagnosed with a primary bone cancer between 1980 and 2005 and registered with one of the 10 regional cancer registries in GB. Main outcome measure: Negative binomial regression was used to examine the relationship between incidence rates and census small-area fluoride levels. These models were fitted to census small-area data aggregated into four age bands (0–14; 15–29; 30–49 and 0–49 years) and by gender with the logarithm of the "at risk" population as an offset. Results: There were a total of 2566 osteosarcoma cases aged 0–49 years; 817 aged 0–14 years; 1315 aged 15–29 years and 434 aged 30–49 years. For Ewing sarcoma there were a total of 1650 cases aged 0–49 years; 659 aged 0–14 years; 800 aged 15–29 years and 191 aged 30–49 years. After adjustment for age and gender, no statistically significant association was found between osteosarcoma or Ewing sarcoma and fluoride levels in drinking water. For example, for osteosarcoma the RR for 1 ppm increase in fluoride level 0.993; 95% CI 0.843 to to 1.171 and for Ewing sarcoma RR 0.860; 95% CI 0.696 to to 1.064. Conclusion: This is the first time the relationship between fluoride and bone cancer has been studied across the whole of GB at census ward level. No statistically significant associations between Ewing sarcoma or osteosarcoma and fluoride in drinking water were found.